2009
DOI: 10.2337/dc08-1297
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Intensification of Oral Diabetes Medications in Primary Care Provider-Patient Dyads: A Cohort Study

Abstract: OBJECTIVE -Although suboptimal glycemic control is known to be common in diabetic adults, few studies have evaluated factors at the level of the physician-patient encounter. Our objective was to identify novel visit-based factors associated with intensification of oral diabetes medications in diabetic adults.RESEARCH DESIGN AND METHODS -We conducted a nonconcurrent prospective cohort study of 121 patients with type 2 diabetes and hyperglycemia (A1C Ն8%) enrolled in an academically affiliated managed-care progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…Many factors contribute to this problem, including competing demands at the time of the visit 3 and medication nonadherence. 4 Rates of treatment intensifi cation when patients are not at goal, however, hover around 70% to 80%, 5 and several studies have linked higher rates of treatment intensifi cation by a primary care physician to better rates of hypertension, lipid, or glucose control in that primary care physician's patients. 6 In theory, treatment intensifi cation and control of hemoglobin A 1c , blood pressure, and lipid levels in patients with diabetes mellitus could be improved by providing patient-specifi c and drug-specifi c clinical decision support at the time of a clinical encounter.…”
mentioning
confidence: 99%
“…Many factors contribute to this problem, including competing demands at the time of the visit 3 and medication nonadherence. 4 Rates of treatment intensifi cation when patients are not at goal, however, hover around 70% to 80%, 5 and several studies have linked higher rates of treatment intensifi cation by a primary care physician to better rates of hypertension, lipid, or glucose control in that primary care physician's patients. 6 In theory, treatment intensifi cation and control of hemoglobin A 1c , blood pressure, and lipid levels in patients with diabetes mellitus could be improved by providing patient-specifi c and drug-specifi c clinical decision support at the time of a clinical encounter.…”
mentioning
confidence: 99%
“…38 While findings continually point to delays in treatment intensification, 39-43 findings of differences in delay length by race have been inconsistent. [39][40][41][42][43] On the other hand, studies of medication adherence have consistently found black patients to be less adherent to prescribed medications. [22][23][24] Our understanding of the impact of medication adherence and treatment intensification to observed racial differences in risk factor control among patients with diabetes remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…For now, it seems that the findings such as those from the Tsukuba Kawai Diabetes Registry study might at least provide another reason for minimising the delays known to occur before glycaemic treatments in type 2 diabetic patients are intensified [16]. Rather than just delaying an improvement in glycaemia, any delay in intensification might also worsen HbA 1c variability, compounding the risk of complications when another agent is eventually introduced.…”
mentioning
confidence: 99%